(untitled) (Heritage, 2022)
The paper explores students’ perceptions of the new learning model imposed on them from March to September 2020 due to the COVID-19 pandemic. This study aims to map students’ cognitive attitudes towards emergency remote teaching (ERT) in order to draw relevant conclusions about whether this practice has been successful in overcoming objective obstacles. Namely, the authors are tasked with exploring the student perspective of a new academic reality and with recording how and how well the students have adapted to ERT. For the purposes of the cross-sectional study, the authors selected three faculties of the University of Priština in Kosovska Mitrovica: the Faculty of Philosophy, the Faculty of Arts, and the Faculty of Medicine. Data are collected by means of a survey, while the respondents are selected by the method of convenient sampling. The results of the study are used to improve teaching practice as well as to assess the readiness of the higher education institution to respond to emergencies in order to maintain the integrity and continuity of the teaching process.